Seasonal Variation of Wet Deposition of Black Carbon in Arctic Alaska. Issue 16 (18th August 2020) - Mori, T.; Kondo, Y.; Ohata, S.; Zhao, Y.; Sinha, P. R.; Oshima, N.; Matsui, H.; Moteki, N.; Koike, M.
Abstract: Black carbon (BC) aerosol deposited in and onto Arctic snow increases the snow's absorption of sunlight and accelerates snowmelt. Wet removal of BC from the atmosphere plays a key role in determining its abundance in the Arctic atmosphere and in Arctic snow. However, this process is poorly understood, mainly due to the scarcity of relevant measurements. To study wet deposition of BC, we made measurements of mass concentration of BC in snow and rain ( C MBC ) and of BC in air ( M BC ) with high accuracy (16% and 10%, respectively) at the Barrow Atmospheric Baseline Observatory, Alaska, from July 2013 to August 2017 and analyzed them along with routinely measured meteorological parameters from Barrow. Monthly mean M BC near the surface and C MBC were poorly correlated from midwinter to early spring, when C MBC was close to the annual median while M BC was at its annual peak. Seasonal variations in the altitude distribution of M BC may lead to these differences in seasonal variation of M BC near the surface and C MBC . About 50% of the annual wet deposition of BC occurred in the 3 months of summer, associated with high values of total precipitation and BC originating from biomass burning. Size distributions of BC in snow and rain were stable throughout the year, suggesting that the size distribution of BC in the lower troposphere was similarly stable. Calculations by two global models reproduced the observed seasonal variations of C MBC and showed that BC from biomass burning dominated C MBC in summer. Plain Language Summary: Black carbon (BC) aerosol, a component of soot, efficiently absorbs solar radiation and heats the atmosphere. BC deposited in and onto Arctic snow increases the absorption of sunlight, accelerates snowmelt, and reduces the snow albedo. Wet deposition of BC greatly influences the concentrations of BC in the atmosphere and in fallen snow. Because measurements of BC wet deposition are scarce, we measured mass concentrations of BC in snow and rain ( C MBC ) and of BC in ambient air near the surface ( M BC ) with high accuracy (16% and 10%, respectively) at the Barrow Atmospheric Baseline Observatory, Alaska, from 2013 to 2017. M BC and C MBC showed different seasonal variations. Differences between BC concentrations near the surface and in the free troposphere may be one cause of this difference. About 50% of the annual wet deposition of BC occurred in the 3 months of summer, associated with high levels of BC emitted from biomass burning and high precipitation amounts. Calculations by two global models reproduced the observed seasonal variations of BC in snow and rain and showed that in summer, this BC was predominantly from biomass burning. Key Points: We studied seasonal variations of black carbon (BC) concentrations in snow and rain in Arctic Alaska using measurements with 16% accuracy About 50% of annual wet deposition occurred in summer, indicating the importance of wet deposition of BC emitted from biomass burning (BB) Model calculations, which reproduce the observed BC in hydrometeors within a factor of 2, suggest large contributions of BB during summer